Servicios de la empresa Ecopallqa S.A.C., consultora especializada en seguridad y salud ocupacional - Montalvo Guevara, María Alejandra (2020)
This professional project includes the planning and implementation of occupational health and safety consultancy services executed during 2017, by the consultancy firm Ecopallqa S.A.C.; for Micro, Small & Medium Enterprises. Currently, Peruvian companies require different services in the occupational health and safety field; either by requirement of government entities, or by fulfilling different standards requirements of markets, suppliers or customers. Likewise, it is very important for companies to have occupational health and safety policies, in order to establish measures to avoid, or at least, minimize risks at work and guarantee their employees safety. This professional project contains five chapters that addressed different aspects related to the consulting firm Ecopallqa S.A.C., of which I am co-founder and shareholder; alongside my partner Victoria Palomino, an Environmental Engineer. Moreover, the details of occupational health and safety services executed during 2017, the year of the company's implementation, were developed. The first chapter: General considerations of the investigation, addresses the preliminary aspects of the company Ecopallqa S.A.C. and the objectives, justification, hypothesis, reference framework and conceptual framework of this professional project. Subsequently, in the second chapter: Situational analysis of the company, the external and internal analysis of Ecopallqa S.A.C. was executed, in addition to the definition of the primary and support activities, and the strategic objectives of the company. In the third chapter: Management, safety, occupational health and environment diagnosis of Ecopallqa S.A.C., the analysis of the service management and the offices location were executed. Moreover, the occupational health and safety assessment, and the identification and assessment of the environmental impact of the organization were carried out. The fourth chapter: Methodology of execution of the services of Ecopallqa S.A.C., describe the tools used for the services management by the company. Subsequently, the fifth chapter: Management of services executed by Ecopallqa S.A.C., includes the initial diagnosis, the methodology planned, the assessment of the results and indicators and the corrective actions proposed for the improvement of the services executed by the company from July to December 2017. Finally, the conclusions and recommendations of this work are detailed.